Financial development, institutions, and economic growth nexus: A spatial econometrics analysis using geographical and institutional proximities - Ahmad, Mahyudin; Law, Siong Hook (John Wiley and Sons, 2023)
This paper investigates the nexus between financial development (FD), institutions, and economic growth using a spatial autoregressive model on a panel dataset of 82 countries from 1990 to 2019. We measure the dependence between countries through geographical and institutional proximity. The latter has not been widely explored in the finance-growth literature. The concept of institutional proximity proposes that countries with similar institutions will have similar levels of economic growth and larger spillovers once spatial effects of FD and institutional quality are controlled. Overall, our findings support this proposition, as FD and political institutions are shown to have significant positive effects on growth. However, the growth-effect of FD becomes negative beyond a certain threshold. We also find significant positive spatial lag growth in the model, indicating the presence of indirect spillover effects of FD and institutions on the growth of neighbouring countries in both geographical and institutional spheres. Furthermore, the spatial growth model with the institutional proximity matrix exhibits a higher rate of convergence and larger size of spillover than the model with geographical proximity. These findings are robust to various model specifications, and the paper concludes with some policy recommendations. © 2023 John Wiley & Sons Ltd.